(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Introduction The aim of this research was to compare SOFA and APACHE II scores for the ability to predict mortality and morbidity among patients of acute poisoning. The secondary aim was to relate these scores with biomarkers of severity to determine their prognostic value. Acute poisoning is one of the most important health problems across the globe, a major contributor to the emergency admissions leading to increased morbidity and mortality. Prognosticating measures like SOFA and APACHE II are essential in prioritizing the patients and planning their management. This study assesses their relative roles in predicting the outcome in patients with acute poisoning presenting to the emergency of a tertiary care hospital in Northern India. Materials & Methods This was a prospective observational study conducted at a tertiary care centre in Northern India , where 85 patients who had acute poisoning were recruited. The severity score tools were applied and they were compared with the severity markers. The performance of the scores was assessed and the sensitivity and the specificity were analyzed using Receiver Operating Characteristic (ROC) curve analysis. Results The SOFA score has been proven to best APACHE II in terms of predictive accuracy. Both scoring systems were found to correlate significantly with NLR, Serum Amylase, and Lactate, with SOFA exhibiting greater sensitivity and specificity. Conclusion SOFA serves better in predicting mortality amongst cases of acute poisoning than APACHE II. Strong correlations with critical biomarkers further reinforce the clinical significance of SOFA score.